Reformulation of Joint Marital Property Regimes for the Protection of Female Migrant Workers: Empirical Evidence from Malang Regency - Syuhadak, Faridatus; Nasrulloh, Muhammad; Sholehuddin, Miftah; Ermawan, Mohamad Zakky Ubaid (UIN Sunan Kudus, 2025)
This article examines the reformulation of joint marital property regimes to enhance legal protection for female migrant workers in Indonesia, particularly in divorce cases in which women are the primary breadwinners. The issue arises from Article 35 of the Indonesian Marriage Law, which grants equal entitlement to husbands over joint property, even when assets are largely generated through women’s overseas employment. Using an empirical juridical method with a descriptive-critical approach, this study analyzes legal norms and their implementation, with a focus on Malang Regency due to its high number of female migrant workers. The findings indicate that equal division of joint property fails to reflect substantive justice and gender equality, often disadvantaging women by requiring them to share earnings with husbands who lack proportional economic contribution. This gap highlights a disconnect between legal norms and social realities. Accordingly, the study recommends an optional application of Article 35, contribution-based property distribution, and enhanced legal awareness by Religious Affairs Offices to ensure substantive justice and effective protection for female migrant workers.